LIME REQUIRMENT TO AMEND RED ACIDIC FISH POND SOILS TO AUGMENT AQUACULTURE PRODCUTIVITY - Datta, Mrinal K; Prakash, Chandra; Saha, Ratan K.; Dhanje, J. R. (Journal of Indian Fisheries Association, 2011)
Physico-chemical quality of red acidic pond soil of Tripura, India was ascertained and the lime requirement was studied following both conventional methodology as well s buffer method to ascertain actual need of quantum of lime for problematic soil. The results indicated acidic nature of both soil and water pH (5.77±0.11 & 6.77) with low Cation Exchange Capacity (2.75±0.32 meq 100g-1) followed by wide C:N ration (20.49±2.27), high AI (5.92±0.57 mg 100g-1) and Fe (3.42±0.26 mg100g-1) contents in soil profile indicating poor productivity of pond soils. Wide variations in lime requirement were noticed and conventional soil pH based methodology exhibited higher lime requirement (622.461 kg ha-1 yr -1 as CaO) than the buffer system (346.371 kg ha-1 yr-1 as Cao) which was almost 50% of actual dose of lime. Accordingly, field experiment was conducted in both old and newly constructed earthen red soil based ponds by liming @300kgha-1. During culture of major carps, rise in pH in old pond (soil 6.22 to 6.5, water 6.75 to 7.35) and new pond (soil 6.22 to 6.5, water 6.75 to 7.35) exhibited slightly acidic to slightly alkaline nature during entire culture period along with major reduction in Fe and AI contents (mg100g-1) as 7.082 to 2.756 and 0.407 to 0.188 respectively. The study contributed the need of soil specific fertilization especially for acidic soils in respect of lime need to enhance aquaculture productivity. Key words: Red acidic soil, Lime requirement, Aquaculture Productivity.